Arab women in arab news old stereotyps and new media - Al-Maliki, Amal Mohamed; Dreher, Kira; Ishizaki, Sugru; Kaufer, David (Doha - =Bloomsbury-Qatar foundation, 2012)
This book addresses east-west understandings of Arab women as portrayed through translated media. The vast majority of media studies on Arab women are western-based. They study the effect of western stereotypes in western media depictions of Arab women. There is a vast scholarly literature tracing western stereotypes of Arab women from medieval times to the present. From 1800, the dominant western stereotype of Arab women depicts them as passive and oppressed. Thirty years of social science media research in the west has shown that media images of Arab women reinforce this two hundred year old stereotype. Much of this research has studied silent "image bites" of Arab women, where women are pictured in veils and their own voices are replaced by western captions or voice-overs
Keywords: This book sets out to answer this question. To answer it, we contracted with a global news translation service from the Middle East to collect and translate a sample of 22 months of new summaries from 103 Arab media sources belonging to 22 Arab countries. Filtering the summaries that contained one or more female keywords (e.g., woman, mother, aunt, sister, she) yielded 2, 061 summaries between September 2005 and June of 2007. Using the 2,061 summaries as input data, a coding scheme was developed for "active" and "passive" female behaviors based on verb-phrase analysis and conventions of English-language news-reporting; Women; Womenʼs rights; women -- Suffrage